2016
DOI: 10.11604/pamj.2016.24.152.7066
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal respiratory distress in a reference neonatology unit in Cameroon: a retrospective analysis of prevalence, predictors, etiologies and outcomes

Abstract: IntroductionNeonatal respiratory distress (NRD) is a main cause of neonatal morbidity and mortality in developing countries. Early detection of its risk factors and early treatment of its etiologies are major challenges. However, few studies in developing countries have provided data needed to tackle it. We aimed to determine the prevalence, predictors, etiologies and outcome of NRD in a tertiary health care centre of Cameroon.MethodsWe analyzed the hospital files of all newborns admitted to the Neonatal unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
66
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 16 publications
(16 reference statements)
22
66
6
2
Order By: Relevance
“…The total cases admitted to our NICU during one year study were 312 cases; of them 145 cases were admitted due to respiratory diseases giving an incidence of (46.5%). This was relatively comparable to the incidence reported by other studies like Verma et al, (39%) and Tochie et al, (47.5%) [11,12]. The present study showed that neonatal respiratory diseases were higher in males (55.9%) than females (44.1%).…”
Section: Discussionsupporting
confidence: 89%
“…The total cases admitted to our NICU during one year study were 312 cases; of them 145 cases were admitted due to respiratory diseases giving an incidence of (46.5%). This was relatively comparable to the incidence reported by other studies like Verma et al, (39%) and Tochie et al, (47.5%) [11,12]. The present study showed that neonatal respiratory diseases were higher in males (55.9%) than females (44.1%).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, sample size, study design, and population socio-demographic characteristics may also lead to the differences observed between studies. Interestingly, the prevalence of RD found in this study was lower than studies from Saudi Arabia (54.7%) [8], Cameroon (47.5%) [7], and Poland (54.29%) [29]. These differences may reflect the quality/qualifications of staff, public awareness to attended births, and cultural beliefs.…”
Section: Plos Onecontrasting
confidence: 86%
“…However, in parallel the increasing rate of caesarian section has led to more recorded cases of RD in full-term neonates [6]. In Cameroon, the General Hospital-Douala team, JN Tochie et al in 2016, reported that RD represented the main cause of neonatal admission (47.5%) in the NCU [7]. Elsewhere, in Nepal, RD contributed a third of NCU admissions, an incidence of around 4% [8].…”
Section: Introductionmentioning
confidence: 99%